Workability and Compressive Strength Behavior of a Cemented High-Porosity Backfill Material - W. H. Cao; X. F. Wang; D. S. Zhang; X. J. Ji; X. Z. Chen; A. Zhang; F. X. Zhu (Advances in Civil Engineering)
A full understanding of the workability and unconfined compressive strength (UCS) of the cemented high-porosity (CHPB) material, made of surface sand, widely distributed in the western mining area, foam, and cementing materials, is important for applying in ecologically fragile mining areas of western China. In this article, the influence of solid content, density grade, sand/binder ratio, and silica fume dosage in binder on workability and strength development of CHPB samples in different curing ages is studied. Test results show that the fresh CHPB mix has good workability, due to the existence of a large number of bubbles. With the increase of density grade, the UCS of the CHPB sample increases exponentially. Workability of fresh CHPB samples significantly decreases with increasing solid content due to the reduction of interparticle distance. For a given mix proportion, the optimal solid content of CHPB samples is 83.7%. The variation of the sand/binder ratio from 3 to 4.5 results in a slight increase of workability and a significant increase of the UCS. Silica fume demonstrates improvement on workability and strength behavior, and the optimal dosage in the binder should not exceed 10%.